Pengaruh Harga, Kualitas Produk, Dan Budaya Terhadap Keputusan Pembelian Produk Mie Instan - Gofur, Iqbal Abdul; Rizal, Mohammad; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research was conducted to determine the influence of price, product quality and culture on purchasing decisions for instant noodle products (Case Study of Santri at the Ainul Yaqin Islamic Boarding School). This research method uses a quantitative method using non-probability sampling techniques and the data source used is primary data by collecting data using a Likert scale questionnaire from students at the Ainul Yaqin Islamic Boarding School who are consumers at the Entrepreneurship Islamic Boarding School. The sample calculation in this study used the Malhotra formula which produced 70 respondents. The data analysis used is descriptive analysis, instrument testing, classical assumptions, multiple linear regression analysis. The results of this research show that price, product quality and culture simultaneously influence the decision to purchase instant noodle products at the Ainul Yaqin Islamic Boarding School. Partially, price has a significant positive effect on purchasing decisions, but product quality and culture do not have a significant effect on purchasing decisions for instant noodle products at the Ainul Yaqin Islamic Boarding School. Keywords: Price, Product Quality, and Culture